(untitled) - Thomas, P. J. (London, 1926)
Mercantilism was the dominant school of thought throughout the early modern period (from the 16th to the 18th century). Domestically, the doctrine led to some of the first instances of significant government intervention and control over the economy, and it was during this period that much of the modern capitalist system.
Keywords: Protectionism,East Indies,Chủ nghĩa bảo hộ,Chủ nghĩa bảo hộ,Đông Ấn; History,Commerce,Lịch sử,Lịch sử,Thương mại; Great Britain,Great Britain,Nước Anh,Nước Anh,Nước Anh